7 - The Taiping and the Aladura: A Comparative Study of Charismatically Based Christian Movements - David Lindenfeld, (Afrika Zamani, 2022)
The paper utilizes the comparative method to work towards an understanding of cross-cultural religious interactions that eschews the distinction between so- called traditional and world religions. It highlights the importance of charis- matic authority based on prophetic vision in two disparate geographical and cultural contexts. Both the Taiping Rebellion (1851–64) and the Aladura churches in southwestern Nigeria in the early twentieth century represented adaptations of Christianity to local circumstances. Although the Aladura churches did not have the politically subversive impact of the famous Chinese rebellion, their popularity as movements of prayer and healing reveal a similar dynamic: of leadership based on visions and extraordinary states of consciousness; rivalries for power based on competing visions; and strategies of routinizing charisma through institutions and Biblical texts. Both movements exhibited a concentra- tion of spirituality, expressed in anti-idolatry and a quest for purity, that mobi- lized energies and led to dramatic change. Jung's theory of withdrawal of pro- jections may better describe this process than Weber's theory of disenchantment.